Automatic device for testing thermal resistance with thermoelectric effect. (March 2020) - Vasiliev, I M; Soldatov, A I; Dementiev, A A; Soldatov, A A; Abouellail, A
Abstract: This paper presents the results of the developed device for testing thermal resistance of thermointerface. Experiments to determine thermal resistance in different cases of thermal interface application were carried out. Dependence of thermoEMF value is obtained, which occurs between semiconductor element body and cooling system radiator at different quality of thermal interface application.